2015
DOI: 10.1177/0883073815576793
|View full text |Cite
|
Sign up to set email alerts
|

The Short-Term Effect of Ketogenic Diet on Carotid Intima-Media Thickness and Elastic Properties of the Carotid Artery and the Aorta in Epileptic Children

Abstract: The aim of this prospective study is to investigate the effect of a 6-month-long ketogenic diet on carotid intima-media thickness, carotid artery, and aortic vascular functions. Thirty-eight drug-resistant epileptic patients who were being treated with ketogenic diet were enrolled. Fasting total cholesterol, high-density lipoprotein, low-density lipoprotein, triglycerides, total cholesterol, and glucose concentrations were measured and echocardiography was performed in all patients before the beginning of keto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…Similar to our findings, many studies reported increased serum levels of total cholesterol, triglyceride, and LDL and decreased serum levels of high density lipoprotein in patients treated with KD (2,5,6,7,16). Whereas, in a single study investigating the effect of KD treatment on serum lipids in 66 healthy obese subjects with a body mass index greater than 30 kg/m 2 , the level of total cholesterol, LDL cholesterol, and triglyceride levels were found significantly decreased, whereas HDL cholesterol ievels significantly increased after the treatment in patients both with and without prior hypercholesterolemia (15).…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 94%
See 4 more Smart Citations
“…Similar to our findings, many studies reported increased serum levels of total cholesterol, triglyceride, and LDL and decreased serum levels of high density lipoprotein in patients treated with KD (2,5,6,7,16). Whereas, in a single study investigating the effect of KD treatment on serum lipids in 66 healthy obese subjects with a body mass index greater than 30 kg/m 2 , the level of total cholesterol, LDL cholesterol, and triglyceride levels were found significantly decreased, whereas HDL cholesterol ievels significantly increased after the treatment in patients both with and without prior hypercholesterolemia (15).…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 94%
“…One of the reason for the absence of cardiovascular adverse effects may be the content of KD in our study; a Mediterranean diet with the major fat being olive oil. Cardioprotective effects of the olive oil have been demonstrated by several studies (2,19,20). In a previous study evaluating the relationship between carotid intima-media thickness and olive oil consumption, carotid intima-media thickness was found to be inversely associated with olive oil consumption in asymptomatic adults with high cardiovascular risk (9).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 96%
See 3 more Smart Citations